Crimean-Congo Hemorrhagic Fever and Autoimmunity: A Georgian Viewpoint Improved by Awareness Survey - BB, Aruna Rajeswari (International Journal of Medical Students, 2025)
BACKGROUND: Crimean Congo hemorrhagic fever (CCHF) is primarily transmitted through the Hyalomma tick a virus found in the Bunyaviridae family. The disease spreads when an individual is bitten by a tick or comes into contact, with one directly. Additionally consuming milk or being exposed to contaminated animal tissues or blood can lead to transmission. While human-to-human transmission can occur through contact with blood or bodily fluids such cases are mostly observed in settings. Around one out of every five individuals infected with the virus shows signs of illness whereas animals and ticks do not exhibit any symptoms of infection. People infected with CCHF typically experience a specific fever at the onset, which may progress rapidly into a hemorrhagic syndrome causing organ failure and potentially leading to death in severe instances. Georgia, located in the South Caucasus region shares borders with countries where CCHF transmission is prevalent. Given that, nearly half of Georgia's population engages in agriculture and resides in areas where they may be at risk, of contracting CCHF. In 2009 the National Electronic Integrated Disease Surveillance System (EIDSS) was introduced to monitor cases in Georgia. Physicians, in healthcare facilities in Georgia suspect a patient may have CCHF and report it to the Georgian National Centre for Disease Control and Public Health through EIDSS, a part of the surveillance system for reporting diseases. METHODS: To study, CCHF information was collected from news media and health publications between 2014 and 2023. Additionally, a cross-sectional survey was conducted to assess peoples’ understanding of CCHF and autoimmunity. The survey consisted of twenty multiple-choice questions covering transmission, symptoms, prevention, and basic autoimmune concepts. The sample of 500 participants ensured representation. Descriptive statistics were utilized to analyze the data for awareness levels and common beliefs. RESULTS: Insights from survey responses collected from individuals in Georgia unveiled intriguing aspects of their awareness and attitudes toward autoimmunity and CCHF. While most participants (60%) were familiar with CCHF it was concerning that 40% could accurately identify the disease transmission methods. Furthermore, the survey indicated that 70% of students expressed worries regarding autoimmunity. However, there seems to be a gap between awareness and understanding of conditions as half of respondents admitted knowing, about them. The difference, in outcomes, demonstrates the impact of campaigns and awareness programs in enhancing students understanding and correcting misconceptions. It underscores the importance of public health strategies that focus on educating people about disorders alongside managing infectious diseases like CCHF. Collaboration among health authorities, schools, and community groups is crucial for bridging knowledge gaps and promoting understanding among students. CONCLUSION: The comprehensive examination of CCHF, in Georgia, enhanced by a study involving adults offers perspectives on existing awareness levels and misunderstandings. Closing these knowledge disparities through focused public health efforts and educational programs is crucial, for empowering individuals to safeguard themselves and their communities from autoimmune conditions.